COMPACTNESS OF S(n)-CLOSED SPACES - Lončar, Ivan (Matematichki Bilten, 2017)
The aim of this paper is to study compactness of the \(S(n)\)-closed spaces. It is proved that \(S(n)\)-closed space \((X,τ)\) is compact if every closed subset of \((X,τ)\) is \(S(n)\)-set and that sequentially \(S(n)\)-closed space \(X\) is countably compact if every closed subset of \(X\) is \(θ^n\)-closed.